Creating a 3D microenvironment for monocyte cultivation: ECM-mimicking hydrogels based on gelatine and hyaluronic acid derivatives - Bystroňová, Julie; Ščigalková, Ivana; Wolfová, Lucie; Pravda, Martin; Vrana, Nihal Engin; Velebný, Vladimir (RSC advances, 2018)
Macrophages play a critical role in the initial response to foreign materials in the body. As most biomaterial-based implantable devices would be treated as a foreign body by the immune system, there is a need for systems that can establish a favourable interaction between the implanted biomaterial and the host. Herein, we describe such a system that can be used as an ECM-like microenvironment for macrophage polarization. The hydrogel system was designed to provide a co-crosslinkable microenvironment containing both protein and glycosaminoglycan components, a hydroxyphenyl derivative of gelatine (GTN-HPA) and tyraminated hyaluronic acid (HA-TA). Both polymers can undergo a crosslinking reaction between polymer chains via the same polymerisation initiation system where the polymer network is formed by crosslinks between phenols in GTN-HPA and HA-TA. The mechanical properties and swelling of the hydrogel can be easily controlled as a function of the crosslinking mode and by the ratio of GTN-HPA and HA-TA compounds used. THP-1 monocytes were successfully encapsulated in the gels and cultured for up to 28 days. Cells exhibited higher metabolic activity when encapsulated in softer hydrogels (E ≈ 10 kPa) compared to stiffer (E ≈ 20 kPa) material in which monocytes tended to form large clusters. Encapsulation of monocytes in the material with HA-TA content enhanced the expression of macrophage-related genes. We demonstrated a co-crosslinkable GTN-HPA and HA-TA matrix microenvironment that is suitable for in vitro micro tissue model applications.